Suicidal Thoughts and Behaviors Among First-Year College Students: Results From the WMH-ICS Project - Mortier, P.; Auerbach, R.; Alonso, J.; Bantjes, J.; Benjet, C.; Cuijpers, P.; Ebert, D.; Green, J.; Hasking, Penelope; Nock, M.; O'Neill, S.; Pinder-Amaker, S.; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Objective College entrance may be a strategically well-placed “point of capture” for detecting late adolescents with suicidal thoughts and behaviors (STB). However, a clear epidemiological picture of STB among incoming college students is lacking. We present the first cross-national data on prevalence as well as socio-demographic and college-related correlates for STB among first-year college students.